1997
DOI: 10.1183/09031936.97.10091967
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and physiological properties of a modified porcine surfactant enriched with surfactant protein A

Abstract: Surfactant protein A (SP-A), a major protein component of natural pulmonary surfactant, is absent in exogenous surfactants currently used in clinical practice.We investigated the physical and physiological properties of one of these modified natural surfactants (Curosurf®) after enrichment with 5% SP-A (SP-A-Curosurf). A pulsating bubble system was used for in vitro assessments and ventilated newborn rabbits for evaluation of in vivo effects.In the presence of various potential inhibitors (meconium 5 mg·mL -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 28 publications
2
24
1
Order By: Relevance
“…The role of SP-A in the resistance to surfactant inhibitors has been demonstrated in previous studies (52). Sun et al (53) reported that in a rat model of MAS, natural porcine surfactant containing 5% SP-A was more effective than the same dose of Curosurf, which contains only polar lipids, SP-B, and SP-C. Addition of SP-A to Curosurf resulted in improved biophysical properties in vitro and better physiologic effects in a rabbit RDS model (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of SP-A in the resistance to surfactant inhibitors has been demonstrated in previous studies (52). Sun et al (53) reported that in a rat model of MAS, natural porcine surfactant containing 5% SP-A was more effective than the same dose of Curosurf, which contains only polar lipids, SP-B, and SP-C. Addition of SP-A to Curosurf resulted in improved biophysical properties in vitro and better physiologic effects in a rabbit RDS model (53).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (53) reported that in a rat model of MAS, natural porcine surfactant containing 5% SP-A was more effective than the same dose of Curosurf, which contains only polar lipids, SP-B, and SP-C. Addition of SP-A to Curosurf resulted in improved biophysical properties in vitro and better physiologic effects in a rabbit RDS model (53). Recently, the possibility that the carbohydrate components of SP-A might be important for resistance to inactivation led Taeusch et al (54) to explore the effects of simple sugars, sugar polymers, and other nonionic polymers on surfactant inactivation by meconium.…”
Section: Discussionmentioning
confidence: 99%
“…Curosurf enriched with 5% SP-A (normally absent in the product) had an increased resistance to inactivation by meconium, fibrinogen, albumin, and serum in vitro and improved pulmonary compliance in immature newborn rabbits after intratracheal instillation of fibrinogen compared with controls treated with only Curosurf (26). In vitro, natural rabbit surfactant (containing about 5% SP-A) was more resistant to inactivation by human meconium than the modified natural surfactants Curosurf, Alveofact, or Survanta (4).…”
Section: Polymyxin B Surfactant and Meconiummentioning
confidence: 99%
“…Firstly, the use of natural surfactants leads to an improved disease outcome, compared with that obtained with synthetic surfactants (14). Secondly, the enrichment of extracted porcine surfactant with SP-A 4 has been shown to prevent inactivation of surfactant function by serum proteins (15). To further understand the surfactant protein components and to initiate research into the protective benefits of surfactant protein in surfactant preparations, the cDNA for porcine SP-D was cloned.…”
mentioning
confidence: 99%